Interaction of the TNFR-receptor associated factor TRAF1 with I-kappa B kinase-2 and TRAF2 indicates a regulatory function for NF-kappa B signaling. - Kalsoom Sughra; Andreas Birbach; Rainer de Martin; Johannes A Schmid (PLoS ONE, 2010)
I-kappa B kinase 2 (IKK2 or IKK-beta) is one of the most crucial signaling kinases for activation of NF-kappa B, a transcription factor that is important for inflammation, cell survival and differentiation. Since many NF-kappa B activating pathways converge at the level of IKK2, molecular interactions of this kinase are pivotal for regulation of NF-kappa B signaling.We searched for proteins interacting with IKK2 using the C-terminal part (amino acids 466-756) as bait in a yeast two-hybrid system and identified the N-terminal part (amino acids 1-228) of the TNF-receptor associated factor TRAF1 as putative interaction partner. The interaction was confirmed in human cells by mammalian two-hybrid and coimmunoprecipitation experiments. The IKK2/TRAF1 interaction seemed weaker than the interaction between TRAF1 and TRAF2, an important activating adapter molecule of NF-kappa B signaling. Reporter gene and kinase assays using ectopic expression of TRAF1 indicated that it can both activate and inhibit IKK2 and NF-kappa B. Co-expression of fluorescently tagged TRAF1 and TRAF2 at different ratios implied that TRAF1 can affect clustering and presumably the activating function of TRAF2 in a dose dependent manner.The observation that TRAF1 can either activate or inhibit the NF-kappa B pathway and the fact that it influences the oligomerization of TRAF2 indicates that relative levels of IKK2, TRAF1 and TRAF2 may be important for regulation of NF-kappa B activity. Since TRAF1 is an NF-kappa B induced gene, it might act as a feedback effector molecule.